Strategi Penanganan Perdagangan Manusia di Wilayah Perbatasan Indonesia - Malaysia - Erika Mayasari; Herlina J.R Saragih; Edy Saptono (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines strategies for addressing human trafficking in the Indonesia-Malaysia border region using qualitative methods through a literature review using a SWOT analysis. Sources include books, scientific journals, articles, research reports, undergraduate theses, dissertations, and various other sources. This is believed to be a contributing factor to the high rate of human trafficking in the border region, such as weak supervision, limited public understanding of the law, and limited infrastructure and coordination between institutions on the Indonesia-Malaysia border. Human trafficking is defined as